Innovation in early modern Catholicism
1 online resource (volumes cm.)
Keywords: "This volume demonstrates that the Catholic rhetoric of tradition disguised both novelties and creative innovations between 1550 and 1700. Re-presenting early modern Catholicism more crucially than any other currently available study, Innovation in Early Modern Catholicism is a useful tool for advanced undergraduates, postgraduates, and scholars in the fields of philosophy, early modern studies, and the history of theology"--